Political Marketing & Future Government - Ramakrishna, B.; Prabhakara Sharma, V. K. (Indian Journal of Marketing, 2004)
The future belongs to students and they naturally have some concern over the future. They always look forward to good government, which shapes their future by providing good education and employment opportunities. People at the center on one hand are boasting that the country is progressing at a greater pace but on the other hand, the government has failed to a major extent in creating employment opportunities for the unemployed youth. Moreover, downsizing the manpower, VRS Computerization are the words that are commonly heard-a-days. Against this backdrop, an attempt has been made to collect the opinion of the PG Students about the present Government both at the Centre and the State. Students’ perception has been collected at micro level study by choosing random sampling technique of certain A.U; Colleges in Srikakulam (town) and Mallampudi (a rural) based areas of coastal Andhra during the poll period of January ’04. The findings have been presented dispassionately.